2014
DOI: 10.3892/or.2014.3489
|View full text |Cite
|
Sign up to set email alerts
|

C5a stimulates the proliferation of breast cancer cells via Akt-dependent RGC-32 gene activation

Abstract: Complement system activation contributes to various immune and inflammatory diseases, as well as cancers.However, the role of complement activation in the proliferation of cancer cells is not clear. In the present study, we investigated the consequences of complement activation on the proliferation of breast cancer cells and its possible mechanisms. We focused our study on the potential roles of the anaphylatoxins C3a and C5a in the proliferation of human breast cancer, as two important immune mediators genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 34 publications
0
17
0
1
Order By: Relevance
“…4). Recently, some studies have reported that Akt activation participated in C5a-induced RGC32 expression in breast cancer cells [30] and hyperglycemia-or hyperinsulinemia-induced RGC32 expression in endothelial cells [31]. Meanwhile, other studies have shown that RGC32 silencing inhibited C5b-9-mediated Akt phosphorylation in human aortic vascular endothelial cells [32].…”
Section: Discussionmentioning
confidence: 98%
“…4). Recently, some studies have reported that Akt activation participated in C5a-induced RGC32 expression in breast cancer cells [30] and hyperglycemia-or hyperinsulinemia-induced RGC32 expression in endothelial cells [31]. Meanwhile, other studies have shown that RGC32 silencing inhibited C5b-9-mediated Akt phosphorylation in human aortic vascular endothelial cells [32].…”
Section: Discussionmentioning
confidence: 98%
“…C5aR1 is expressed in many cells, including in lung alveolar and airway epithelium as well as the endothelium (27, 28). C5aR1‐mediated divergent signaling leads either to apoptosis or cell survival, via ERK (29), Akt activation (30), PKC‐mediated IL‐8 release by the airway epithelium (31), or fibrosis in other organs (32, 33) compared with C5aR2, which is implicated in acute inflammation (34, 35) and balances the biologic responses to C5a (36, 37). Whereas the pathogenesis of acute lung injury has been associated with the destructive effects of C3aR‐dependent (38) and C5aR‐dependent signaling (5, 38, 39) and with the extracellular histone‐dependent signaling of C5aR1/2 (35), the protective effects due to the blockade of C3aR and C5aR1 in airway hyper‐responsiveness and inflammation (40) as well as in renal injury/fibrosis are known (33, 41).…”
mentioning
confidence: 99%
“…in 19983. It plays important roles in the regulation of cell differentiation, angiogenesis, migration, and invasion456. In addition, emerging evidence has revealed that RGC32 is involved in lung cancer7, breast cancer8, hepatic steatosis9, and multiple sclerosis10.…”
mentioning
confidence: 99%